The association between inhaled corticosteroid and the risks of SARS-COV-2 infection: A systematic review and meta-analysis - Chao-Hsien Chen; Ching-Yi Chen; Chih-Cheng Lai; Ya-Hui Wang; Kuang-Hung Chen; Cheng-Yi Wang; Yu-Feng Wei; Pin-Kuei Fu (Elsevier, 2023)
Background: The effect of inhaled corticosteroid (ICS) on the risk of severe acute respiratory syndrome coronavirus 2 (SARS-COV-2) infection is unclear. Methods: We performed a systematic review and meta-analysis of clinical studies that assessed the association between the use of ICS and the risk of SARS-COV-2 infection. PubMed, Web of Science, Scopus, Cochrane Library and Google Scholar were searched to January 1st, 2023. ROBINS-I was used to assess risk of bias of included studies. The outcome of interest was the risk of SARS-COV-2 infection in patients and odds ratio (OR) with 95% confidence interval (95% CI) were calculated using Comprehensive Meta-analysis software version 3. Results: Twelve studies involving seven observational cohort studies, three case-control studies, and two cross-sectional studies were included in this meta-analysis. Overall, compared to non-ICS use, the pooled odds ratio (OR) of the risk of SARS-COV-2 infection was 0.997 (95% confidence interval [CI] 0.664-1.499; p = 0.987) for patients with ICS use. Subgroup analyses demonstrated no statistical significance in the increased risk of SARS-COV-2 infection in patients with ICS monotherapy or in combination with bronchodilators (pooled OR=1.408; 95% CI=0.693-2.858; p = 0.344 in ICS monotherapy, and pooled OR=1.225; 95% CI=0.533-2.815; p = 0.633 in ICS combination, respectively). In addition, no significant association was observed between ICS use and the risk of SARS-COV-2 infection for patients with COPD (pooled OR=0.715; 95% CI=0.415-1.230; p = 0.225) and asthma (pooled OR=1.081; 95% CI=0.970-1.206; p = 0.160). Conclusions: The use of ICS, either monotherapy or in combination with bronchodilators, does not have impact on the risk of SARS-COV-2 infection.